Fertigung qualitätsoptimierter Spaltprofile durch Variation schnell änderbarer Prozessgrößen und deren Einfluss auf die Materialeigenschaften. Issue 7 (16th July 2013) - Ludwig, C.; Hammen, V.; Groche, P.; Kaune, V.; Müller, C.
<x xml:space="preserve">Abstract</x> The bulk forming process linear flow splitting is on its way from research under laboratory condition into industrial production. Because of that, in particular questions about process stability at high production rates and varying lubrication condition occur. Besides modifications of geometry a change in material characteristics is in the focus of interest. Within this article the impact of varying strip speed, strip tension and lubrication amount on the profile geometry is described quantitatively. From these results it is obvious, how far a manipulation of the profile geometry is possible by the process factors. Also microstructures, hardness profiles and textures of the linear flow split profiles are presented, which were received under different process conditions. Using statistical methods, in particular the uni‐ and multivariate regression analyses, an analytic description for the prediction of induced profile geometries based on the experimental results is given. This opens the possibility of a direct control on part geometry by the before identified influencing variables.